2015
DOI: 10.1007/s00701-015-2485-6
|View full text |Cite
|
Sign up to set email alerts
|

Sphenoid sinus aspergilloma in trans-sphenoidal surgery for pituitary adenomas

Abstract: Sphenoid sinus aspergilloma can be found during trans-sphenoidal surgery for pituitary adenomas. Sphenoid sinus extirpation followed by adenomectomy is the treatment of choice unless invasive aspergilloma is encountered requiring additional antifungal therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Isolated sphenoid sinusitis is rare and seen in fewer than 3% of all sinusitis. Patients with isolated fungal infection are rarer and considered as non-invasive, indolent form of fungal sinusitis 7. Viral or bacterial infection of the sphenoid sinus can provide sufficient nutrients to the fungi, which start proliferating in a low pH medium, and sometimes forming a fungal ball 8…”
Section: Discussionmentioning
confidence: 99%
“…Isolated sphenoid sinusitis is rare and seen in fewer than 3% of all sinusitis. Patients with isolated fungal infection are rarer and considered as non-invasive, indolent form of fungal sinusitis 7. Viral or bacterial infection of the sphenoid sinus can provide sufficient nutrients to the fungi, which start proliferating in a low pH medium, and sometimes forming a fungal ball 8…”
Section: Discussionmentioning
confidence: 99%
“…Aspergillus often affects immunocompromised hosts such as those on oral immunosuppressant drugs after organ transplantation. [ 15 ] Hypercortisolemia secondary to Cushing disease also suppresses the immune system. Dubey has reported that diabetes mellitus was the most immunocompromising factor, presents in 40% of their cases with fungal infections.…”
Section: Discussionmentioning
confidence: 99%
“…2 Sphenoid sinus mycetomas are known to mimic pituitary adenomas, especially when associated with an atypical presentations, previous history of sellar surgery and appearance in immunocompetent patients. [1][2][3] Endonasal transsphenoidal approach has been a wellestablished method for pituitary gland tumor surgery. Complications of endonasal transsphenoidal surgery are epistaxis, septal perforation, sinusitis, and atrophic rhinitis, relatively not life-threatening compared to open craniotomy.…”
mentioning
confidence: 99%
“…1 Isolated fungal sphenoid sinusitis is also rare and is considered as indolent, noninvasive form of fungal sinusitis, without the need for antifungal therapy following surgery. 2 Sphenoid sinus mycetomas are known to mimic pituitary adenomas, especially when associated with an atypical presentations, previous history of sellar surgery and appearance in immunocompetent patients. [1][2][3] Endonasal transsphenoidal approach has been a wellestablished method for pituitary gland tumor surgery.…”
mentioning
confidence: 99%
See 1 more Smart Citation